2021
DOI: 10.1021/acs.macromol.1c00884
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse Liquid Crystalline Polymer Shells with Programmable Alignment and Shape Prepared by Seeded Dispersion Polymerization

Abstract: Monodisperse liquid crystalline polymer shells with programmable alignment and shape prepared by seeded dispersion polymerization. Macromolecules, 54(13), 6052-6060.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This is different to the above-mentioned one-step polymerization methods, in which the surface concavity is formed directly in the polymerization process. Both hard templates [140][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157] and soft templates [158][159][160][161][162][163][164][165][166] have been used for the preparation of dimpled polymer particles.…”
Section: Templating Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is different to the above-mentioned one-step polymerization methods, in which the surface concavity is formed directly in the polymerization process. Both hard templates [140][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157] and soft templates [158][159][160][161][162][163][164][165][166] have been used for the preparation of dimpled polymer particles.…”
Section: Templating Methodsmentioning
confidence: 99%
“…It is worth emphasizing that dimpled polymer capsules can be conveniently fabricated by the "collapse" of the spherical capsules, which are formed by removing the core templates from the core-shell particles. [152][153][154][155][156][157] For example, Zhou and co-workers reported that polydopamine (PDA) nano/microcapsules could be readily produced by the formation of PDA on the template surface, followed by removal of the template. [152] When the diameter of the capsule reached to 2 mm, bowl-like capsules were observed due to collapse.…”
Section: Templating Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such bipolar configuration has been observed in spherical liquid crystalline polymer particles 29,30 and nonspherical particles derived from spherical particles using liquid crystal templates 31 or seeded particles. 32 The preparation of oblate polymer particles generally requires multistep procedures such as the mechanical squeezing or stretching of spherical particles. 34,39 In contrast, the direct preparation of nonspherical polymer particles by the heterogeneous polymerization of a single monomer has been rarely reported.…”
Section: Preparation and Characterization Of Crosslinked Azobenzene P...mentioning
confidence: 99%
“…1d) was identified under the crossed nicols. 42 The bright-field spots gradually disappeared with increasing contents of hydroxyl groups (see Fig. S8 †).…”
mentioning
confidence: 95%